Investigation of renal tubular function with newly diagnosed type 1 diabetes mellitus during diabetic ketoacidosis - Naonori Kumagai; Hiroki Takao; Yuta Sudo; Masatoshi Yoshikane; Tomomi Kondoh; Yuji Matsumoto; Haruo Mizuno; Michiaki Abe; Yohei Ikezumi (Diabetology & Metabolic Syndrome)
Abstract Background Proximal renal tubular dysfunction occurs during diabetic ketoacidosis (DKA) in type 1 diabetes. However, only a few studies have reported on the multiple proximal renal tubular functions simultaneously. Moreover, to the best of our knowledge, distal renal tubular function has not yet been investigated. Methods Patients with newly diagnosed type 1 diabetes mellitus were classified into those with DKA and those without DKA, and their proximal and distal renal tubular functions were investigated. The diagnostic criteria for DKA were blood glucose > 200 mg/dL, blood pH < 7.3 or HCO3 – < 15 mEq/L, and urine ketone body positivity. Results Six patients with DKA and five patients without DKA were included. In patients with DKA, urinary β2-microglobulin levels were significantly higher, while blood pH, HCO3 –, and tubular reabsorption of phosphorus were significantly lower than in those without DKA. There were no significant differences in blood glucose, HbA1c, serum phosphorus, urinary N-acetyl-beta-glucosaminidase, and urinary amino acid excretion between patients with and without DKA. Elevated NH3 levels and impaired urinary acidification were not observed in patients with and without DKA. Conclusions In patients with newly diagnosed type 1 diabetes mellitus complicated with DKA, multiple proximal renal tubular dysfunctions occur simultaneously, suggesting transient Fanconi syndrome. Distal renal tubular acidosis was unlikely. The diagnostic criteria for DKA are appropriate also in the view of proximal renal tubular dysfunction and are considered suggestive of pathophysiological factors that may cause proximal renal tubular dysfunction.